On the effects of the design of cable-Driven robots on kinematics and dynamics models accuracy. (May 2017) - Gonzalez-Rodriguez, A.; Castillo-Garcia, F.J.; Ottaviano, E.; Rea, P.; Gonzalez-Rodriguez, A.G.
Abstract: This paper tackles the problem of improving the connection between the fixed frame and the end-effector of planar and spatial cable-driven robots. A new design concept is detailed, which consists in adding pulleys to the attachment between the cables and the end-effector. These reflective pulleys must have the same radius as the ones at the frame in order to compensate their geometry. Without this modification in the end-effector, the usual simplification of the point-to-point method used to model the connection between frame and end-effector leads to significant errors in the Kinematics and Dynamics of the system due to the fact that the geometry of the frame pulleys is disregarded. By adding the reflective pulleys in the end-effector, the equations of the Kinematics and Dynamics of the real system are equivalent to those of the point-to-point model, and therefore, this simplified method can be used without inherent errors. This solution may be of great importance for computational issues because it leads to codes that may run at real time. An analytical proof of the equivalence of both models is presented. Finally, experimental results have been conducted for both, planar and spatial cable-robots, in order to illustrate the advantages of using this novel design concept for the connection between the end-effector and the fixed frame.